Dynamics of Ethno-Social Structure and Social Wellbeing of Population in Polyethnic Region (by Example of Republic of Bashkortostan) - F. G. Safin (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The issue of ethno-social structure dynamics and ethno-social wellbeing of the population in the Republic of Bashkortostan is considered on the basis of the results of the censuses and data of ethno-sociological surveys conducted in 1989-2010 in the region. Special attention is paid to the representation of a particular ethnic group in the leading sectors of industry, administration, education. For a better vision of ethno-social development of the Republic in general the tables with data on types of economic activities and social identification are given. The results of a comparative analysis of social structure of the major ethnic groups of Bashkortostan are presented: Russians, Bashkirs, Tatars. The paper raised the question of their unequal access to power and management structures, to the budget places in universities etc. An attempt was made to prove the direct influence of the transformation of ethno-social structure on social well-being of the population and their correlation. The authors come to the conclusion that fundamental changes that occurred during the market economy brought about changes in ethno-social population structure. There are new social stratas (classes), which in the scientific literature began to be divided according to their social status and well-being.